2013
DOI: 10.1002/aenm.201300240
|View full text |Cite
|
Sign up to set email alerts
|

Triazatruxene‐Diketopyrrolopyrrole Dumbbell‐Shaped Molecules as Photoactive Electron Donor for High‐Efficiency Solution Processed Organic Solar Cells

Abstract: Stepwise construction of functional triazatruxene platforms allow linking to preorganized diketopyrrolopyrrole bearing thienyl subunits. These dyes exhibit strong absorption until 750 nm in thin films and show favorable redox activity allowing producing efficient organic solar cells when blended in solution with PC71BM. A maximum power conversion efficiency of 5.3% was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…The idea was to use the TB 2 scaffold in order to obtain TAT‐BODIPY‐TAT arrangements. Incidentally, TAT‐dye‐TAT compounds have been subject of recurrent publications from this research team and showed promising results when exploring different central electron‐poor units such as DPP . The difference between BVT and BET lies in the conjugated linker used to connect TAT units with BODIPY at the 2‐ and 6‐positions.…”
Section: Bodipy In Bhjmentioning
confidence: 99%
“…The idea was to use the TB 2 scaffold in order to obtain TAT‐BODIPY‐TAT arrangements. Incidentally, TAT‐dye‐TAT compounds have been subject of recurrent publications from this research team and showed promising results when exploring different central electron‐poor units such as DPP . The difference between BVT and BET lies in the conjugated linker used to connect TAT units with BODIPY at the 2‐ and 6‐positions.…”
Section: Bodipy In Bhjmentioning
confidence: 99%
“…It shows end-to-end π-π interactions in the solid phase and leads to favorable active layer morphologies with low ratios of fullerene acceptors. With a 1:0.75 2j:PC 70 BM weight ratio, solar cells demonstrated a high PCE of 5.3 % with a V OC of 0.63 V and J SC of 14.6 mA cm −2 after thermal annealing (110°C for 20 min) [33]. Using a naphthadithiophene donor group as the core and DPP as terminal arms, an alternative A-D-A (Acceptor-Donor-Acceptor) structure (2K) was employed by Marks et al Solar cells prepared from a 2K:PCBM (1.5:1.02) deliver a high PCE of 4.06 %, with a V OC of 0.84 V, J SC of 11.27 mA cm −2 , and FF of 0.42 by annealing at 110°C for 10 min [34].…”
Section: Dyesmentioning
confidence: 99%
“…In general, the donor–acceptor blended film is amorphous. Thus, exciton diffusion length is very small, typically, in a range of 5–20 nm for most organic semiconductors . To boost charge separation, it generally requires the blended donor and acceptor to form nanoscale aggregate domains with the phase size comparable to the exciton diffusion length, so that the excitons can efficiently reach the donor–acceptor interface via the concentration‐ingredient driving diffusion process .…”
Section: Introductionmentioning
confidence: 99%